Influence of Health Promotion in Exclusive ASI Providing in the Working Area of the Hamparan Puskesmas Perak Deli Serdang District - Jelita, Nenny; Asriwati, Asriwati; Nasution, Ramadhani Syafitri (PT. Riset Press International, 2024)
Breast milk that is not given optimally to babies will have an impact on low nutrition and growth in babies. This can be prevented by giving exclusive breast milk for six months from the first hour after the baby's birth without being given any additional food or drink. The aim of this research is to determine the effect of health promotion on exclusive breastfeeding in the Hamparan Perak Community Health Center Working Area, Deli Serdang Regency. This research method is quasi-experimental with a population of mothers in the Hamparan Perak health center working area with a sample size of 93 respondents. The results of this research are that there is an influence of health promotion on knowledge, culture, information, before and after giving exclusive breastfeeding in the working area of ​​the Tanjung Perak Health Center, Deli Serdang Regency with a p-value of 0.000; 0.002; 0.001 and <0.05. The conclusion of this research is that there is an influence of health promotion on knowledge, culture, information before and after giving exclusive breastfeeding. It is hoped that respondents will be able to find out by taking part in scientific activities, hoping to slowly change mothers' mindsets towards culture, it is hoped that mothers will be able to take part in discussions to find out about the latest information regarding exclusive breastfeeding.